System Dynamics-Based Industrial Modeling of Aluminium Processing in Indonesia - Rafli Al Hadi; Fergyanto E Gunawan (Advance Sustainable Science Engineering and Technology, 2026)
The Indonesian aluminum industry has great potential due to its abundant bauxite reserves, but downstream development to increase added value is still limited. This study uses a dynamic system model to simulate the development of Indonesia's aluminum industry, taking into account variables such as bauxite reserves, production capacity, demand, energy costs, raw material prices, and downstream development barriers. A scenario-based simulation method is applied to evaluate the impact of various policies, including import substitution, increased production capacity, and the use of coal-fired electricity in aluminum smelting plants. The simulation results show that the optimal scenario produces total emissions of 158,276 tons of CO₂eq, total profits of USD 48,321.60 million, and energy consumption of 22,075,800 MWh, which is more efficient than other scenarios. The contribution of this research lies in providing a technical framework for dynamic system modeling to support more measurable and sustainable downstream aluminum industry strategy planning.